Gubernur di Ujung Jari: Bagaimana Ganjar Pranowo Merevolusi Pengaduan Publik Melalui Twitter - Purwadi, Anton; Sanjaya, Natta; Nugraha, Joko Tri (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
This study measures the dimensions of responsiveness of the Central Java Provincial Government and its impact on citizen satisfaction, adopting the theoretical framework of good governance. Employing a mixed-methods approach that combines in-depth interviews with big data analysis crawled from the provincial government's official Twitter account using Python on the Google Colab platform this study finds that the government has effectively realized the principle of responsiveness. Complex complaints, such as alleged illegal levies and bureaucratic complexities, were resolved in under three days, a timeframe comparable to the resolution of infrastructure-related issues. Another key finding reveals a strategic communication model employed by citizens, which involves consistently tagging the Governor's account to expedite the resolution process. However, this model creates a systemic vulnerability, as it is highly person-centric and dependent on an individual figure. This dependency threatens the program's long-term effectiveness and sustainability, particularly in the event of a leadership change. Therefore, the study recommends the institutionalization of the system through Standard Operating Procedures (SOPs) and robust governance structures to ensure its continuity. governance.